(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: The use of disposable diaper is gradually increasing for the infants in our country. However, the major hazard of diaper is diaper dermatitis. The magnitude of diaper related hazards is unknown in Bangladesh. This study was conducted to assess the frequency of hazards of wearing diaper among infants. Objectives: The study was conducted (i) to observe diaper related hazards among infants and (ii) to assess the factors affecting diaper related hazards. Materials and Methods: This observational study was conducted at department of Pediatrics of Dhaka Medical College Hospital & Bangabandhu Sheikh Mujib Medical University during May to September 2012. Fifty children aged 7 days to 12 months wearing disposable diaper for at least 7 days were enrolled in this study. A face to face interview was taken and finding were recorded on a preset questionnaire. The infants were also examined for presence of diaper rash. Obtained data were analyzed thoroughly by SPSS 21. Results: Among 50 children, 24(48%) male and 26(52%) female infants. Of them 13(26%) infants developed diaper rash in their diaper wearing time. The age distribution of the cases was 3(23.1%) below 01 months; 2(15.3%) 1-6 months and 8(61.6%) 7-12 months. Six (24%) male infant and 7(27%) female infant developed rash in their diaper wearing time. Diapers are mostly used by solvent families as diapers are not cost effective. The frequency 84.6%, increases with increased duration of using a single diaper at a time for more than 4 hours without change whereas those who changed diaper more frequently every 3-4 hours and 1-2 hours have diaper rash 15.4% and 0% respectively. Conclusion: From the result of the present study it can be concluded that the frequency of diaper rash is increased with increasing age of infants and use of diaper for long duration. J Bangladesh Coll Phys Surg 2017; 35(4): 170-173